„Dirty Hands” versus „Clean Models”, czyli o potrzebie międzydyscyplinarnych badań w ekonomii i socjologii. Nowe imperatywy badawcze w naukach społecznych - Morawska, Wiktoria (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The aim of the article is to present new challenges of sociology and economics — entangled in the context of globalization, market segmentation, and the so-called consumer society. The effect of these changes is the need to make interdisciplinary exploration of new research areas an imperative. The article contains a cross-sectional, historical outline of economic sociology and the reasons for the development of the heterodoxic currents of economics. This applies to the critical analysis of economy and the problems of its polarization according to S. Sassen, the theory of social rooting of the economy by M. Granovetter, sociology of economy at Harvard University, models of W. Morawski, or the “dirty hands” and “clean” models of P. Hirsch, S. Michaels, and R.Friedman. The most important value is demonstrating the need for interdisciplinarity in modern economics and redefining the position of disciplines with low social prestige; including them in the mainstream research. It became crucial to reject the discourse on generating and defining discipline boundaries. The imperative adopted in this way results from the belief that contemporary reality requires not only an economic analysis, but also the metaphorical “joining of forces” within humanities, social, as well as hard sciences.
Keywords: economic sociology; globalization; sub-discipline; science; interdisciplinarity